Trauma Representation in Kazuo Ishiguro's Never Let Me Go: A Narrative Study Based on Cathy Caruth's Theory - Maslida, Nathania Reva; Wajiran, Wajiran (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
This study aims to examine the representation of personal and collective trauma in the novel Never Let Me Go by Kazuo Ishiguro using the trauma theory approach developed by Cathy Caruth. Trauma in this context is understood not simply as a painful experience, but as an event that cannot be understood directly and only reappears in the form of repetition, dissociation, and disruption in the narrative structure. This research uses a qualitative-descriptive method with content analysis techniques of the novel text, supported by literature studies of relevant academic sources. Data were collected through in-depth reading techniques and analyzed thematically based on Caruth's key concepts such as belatedness, deferred understanding, and repetition compulsion. The analysis shows that the characters' traumatic experiences are not only personal, but also reflect collective wounds institutionalized through a dystopic social system. The non-linear narrative structure, the fragmentation of the characters' identities, and the delayed understanding of their fate are the main markers of the traumatic experience. This study concludes that Never Let Me Go not only depicts trauma through the content of the story, but also through the narrative form that reflects the psychological mechanism of trauma. This finding reinforces the importance of reading trauma in understanding the ethical and human dimensions in contemporary literature.